2016
DOI: 10.1016/j.ijheatmasstransfer.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical consideration of contact angle hysteresis using surface-energy-minimization methods

Abstract: a b s t r a c tIn recent years, advances in coating manufacturing processes have allowed wetting characteristics of a surface to be tuned with micro/nano morphologies. Today, complex surface geometries can be created with various surface treatment methods. These advances can be implemented in phase-change heattransfer applications, such as condensation, which relies on droplet behavior on a surface. Therefore, it is important to gain a fundamental understanding of wetting characteristics of textured surfaces h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…On the contrary, when the contact angle ranges from 90° to 180°, the contact angle will be greater due to the e ects of pore wall roughness. at is, roughness will make the hydrophilic surface more hydrophilic, and make the hydrophobic surface more hydrophobic [36][37][38][39]48]. e apparent contact angle can be expressed by the Wenzel equation [34] where is the apparent contact angle a ected by wall roughness, is a surface roughness factor that equals to the ratio of the actual area to project area.…”
Section: Surface DI Usionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, when the contact angle ranges from 90° to 180°, the contact angle will be greater due to the e ects of pore wall roughness. at is, roughness will make the hydrophilic surface more hydrophilic, and make the hydrophobic surface more hydrophobic [36][37][38][39]48]. e apparent contact angle can be expressed by the Wenzel equation [34] where is the apparent contact angle a ected by wall roughness, is a surface roughness factor that equals to the ratio of the actual area to project area.…”
Section: Surface DI Usionmentioning
confidence: 99%
“…e roughness makes the e ective contact angle smaller which results in the decrease in slip length when contact angle ranges from 0° to 90°. When the contact angle ranges from 90° to 180°, the e ective contact angle increases as the roughness increases [36][37][38][39]. For the e ects of gas lms or trapped gas on the pore wall, Ruckenstein and Rajora [23] proposed that the water could ow on the wall with gas lms, and the slip length would be larger considering gas lms [40].…”
Section: Introductionmentioning
confidence: 99%
“…When the contact angle is lower than 90°, the surface is considered hydrophilic, and if the contact angle is higher than 90°, the surface depicts hydrophobic characteristics. Engineered surfaces, those with hydrophobic and hydrophilic combined characteristics, have been studied by several researchers [16]…”
Section: Contact Angles On Distinctive Surface Wetting Propertiesmentioning
confidence: 99%
“…They found that the advancing contact angle remained constant as independent of capillary number, while the dynamics receding contact angle decreased with increasing capillary number. Cheng et al [20] proposed a mathematical model to determine the contact angle hysteresis by employing concepts of surface-energy minimization. The model can predict contact angle hysteresis of droplets on di erent surface geometries and degrees of wetting.…”
Section: Introductionmentioning
confidence: 99%